Pilot evaluation of PrEP EmERGE – A novel digital health innovation designed to support sexual health clinics and HIV‐PrEP users. Issue 4 (22nd September 2022) - Fitzpatrick, Colin; Richardson, Daniel; Sherriff, Nigel; Whetham, Jennifer
Abstract: Objective: We aimed to evaluate the usability and acceptability of a co‐designed mobile health (mHealth) application (PrEP‐EmERGE) within a digital health pathway to support HIV pre‐exposure prophylaxis (PrEP). Methods: This was a cross‐sectional study to evaluate the usability and acceptability of the PrEP‐EmERGE app. Data were collected via an online survey sent to all PrEP EmERGE users in September 2021. Usability was assessed with a validated usability tool, the System Usability Scale (SUS). Acceptability was assessed using modified patient‐reported experience measures (PREMs). Quantitative data were analysed using descriptive and/or inferential statistics and qualitative data (free text responses) using thematic analysis. Results: In total, 81/133 (61%) active PrEP EmERGE users completed the online survey, which was available directly from their PrEP EmERGE app: 78/81 (96%) identified as cis‐male, 74/81 (91%) reported their ethnicity as 'white', 69/81 (85%) reported daily PrEP use, 7/81 (9%) reported using an event‐based dosing schedule, and 5/81 (6%) were switching between dosing schedules. Overall, the median SUS score was 78/100 (interquartile range: 70–92). There were no differences in median SUS scores by PrEP dosing schedules ( p  = 0.78) or months of experience of using the app ( p  = 0.31). Overall, 73/81 (90%) would recommend the PrEP EmERGE app to a friend and 78/81 (96%) rated their satisfaction of the app as excellent, good or satisfactory. The free text responses generated three key themes: accessibility (for results and information); autonomy [taking responsibility for their (sexual) health] and functionality (including technical recommendations for app development and the digital health pathway). Conclusions: Innovative, co‐designed digital health pathways, such as PrEP EmERGE can help sexual health services to manage increasing numbers of people accessing PrEP – ensuring that they retain access for those who need to be seen face‐to‐face. We report high levels of acceptability and usability during the first 4 months of this novel pathway.